(untitled) (Linguostylistic Studies, 2015)
The article is an attempt to analyze the specificity of vocabulary and phraseology of the most ancient printed monument of Volyn writing – «Liament…» (1628). Regional cultural memorials (handwritten and printed) occupy primarily a prominent place among the sources of the national spiritual culture history of Ukraine. The first printed edition of «Liament for the father Ivan Vasylovych» (1628) belongs to the earliest written sources of Volyn. The language of the monument reflects the features of vocabulary and phraseology of the genre «liamenty» of middle of the XVII century. Key words: spiritual culture, monuments of Ukrainian writing, plaintive poetry, old Ukrainian vocabulary and phraseology. References